THE INFLUENCE OF HEDONIC SHOPPING MOTIVATION AND SHOPPING LIFESTYLE ON E-IMPULSE BUYING OF LAMONGAN ISLAMIC UNIVERSITY STUDENTS AT SHOPEE.CO.ID - Nucha, Lailatun; Azizah, Luluk Nur; Khitam, Muhammad Chusnul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The ease of getting information about goods in e-commerce, especially shopee, encourages consumers to always want to shop for their lifestyle and to fulfill needs that they don't have or shop hedically, that is a factor for someone to take impulse buying. This study aims to determine the influence of hedonic Shopping Motivation and Shopping Lifestyle partially, simultaneously and dominantly towards Impulse Buying at Shopee.co.id. The population used was 6,016 of the number of students at Lamongan Islamic University, with a sample size of 100 using purposive sampling technique. The method used in this study was the Quantitative Descriptive Method, with the test tools being validity test, reliability test, multiple linear regression test, correlation test. Multiple, Determination Coefficient Test, T test, and F test. The results showed that the variables Hedonic Shopping Motivation (X1) and Shopping Lifestyle (X2) had a partially significant effect on impulse buying. this is shown by the calculation results of the t test obtained by the variable values ​​of Hedonic Shopping Motivation (4.925), and Shopping Lifestyle (6.668) > 1.660. So rejected and accepted. Whereas in the calculation of the F Test there is a simultaneous influence as evidenced by the value of 87.691 > 3.09 So it is rejected and accepted. Based on the calculation of Multiple Linear Regression in the model Y = 3.783 + 0.215X1 + 0.308X2. It is found that the most dominant variable on Impulse Buying is Shopping Lifestyle (X2) with a regression coefficient value of 0.308. While other variables show numbers below 0.308, namely the variable Hedonic Shopping Motivation (X1) with a value of 0.215.